Developing and demonstrating a maturity model for smart ports. Issue 4 (19th May 2023) - Boullauazan, Yassin; Sys, Christa; Vanelslander, Thierry
ABSTRACT: Increasing congestion and the push for (i) a greener modal shift, (ii) more reliability and visibility of goods, and (iii) more sustainable activities in and related to the port are turning policymakers to the concept of the smart port. Such emerging concept describes a future state of the port that is adapted to these challenges. A smart port is a port that optimizes in-, intra- and outbound flow of goods and information, leads sustainable development and guarantees safe, resilient and secure activities through the capabilities of its (extended) port community and enabling technologies. However, turning a traditional port into a smart port is a strategic challenge for the port community at large. To contribute to this practically relevant and academic challenge, the present paper applies a literature review and the novel maturity model development methodology to develop a strategic tool. This newly-developed strategic tool (i) enhances the common understanding of the current and aspired maturity state, (ii) support decision-making of port policy and management actors and (iii) represent a maturation path for improvement for port communities. The case study results demonstrate the benefits and relevance of the tool. Finally, recommendations are made to apply this policy tool for digitalization strategy.